Determinant of Pharmaceutical Industries Marketing Performance in Indonesia - Limakrisna, Nandan; Adriza, Adriza; Zahara, Rita (International Review of Management and Marketing, 2017)
The purpose of this research is to determine and analyze the model of competitive advantage and marketing performance. Methods/ Analysis used in this research was a descriptive survey and explanatory survey methods with a sample size of 285 respondents using proportional random sampling. Data collecting use questioners and observation, and the data analysis methods used are SEM (Structural Equation Modeling). Findings of this reseach is buyers relationship, suppliers relationship, and company resources have positive and significant influence on competitive advantage. Buyers relationship partially dominant effect on competitive advantage. Buyers relationship, suppliers relationship, company resources and competitive advantage have positive and significant effect on the marketig performance. Company resource partially dominant effect on marketing performance. This research result are helpful in adding more value of Pharmaceutical industry, so the company can improve their company resources for increasing ther marketing performance. Application/ Improvement in this research, company resources be importance for increasing marketing performance, but in the others research generally competitive advantage more importance. Keywords: Relationship, Company Resources, Marketing Performance JEL Classification: M21